Java 8 lambdas and streams : introduction to functional programming in Java - Konda, Madhusudhan (O'Reilly, 2015)
"In this Java 8 Lambdas and Streams training course, expert author Madhusudhan Konda will teach you how to develop Java applications using Java 8. This course is designed for users that already have experience with Java. You will start by learning about lambdas, including the lambda syntax, target typing, and lambda scoping. From there, Madhu will teach you about interfaces, functions, streams, and stream common operations. This video tutorial also covers advanced streams, including grouping, partitioning, and flat map. Finally, you will learn about parallel streams, including serial execution, sequential or parallel, and performance measurements. Once you have completed this computer based training course, you will have gained a solid understanding of functional Java programming."--Resource description page.